Clinical and radiological profile of patients with cerebral venous and sinus thrombosis in a tertiary care hospital - Vidyasagar, Sudha; Peddu, Aasish; Bolanthakodi, Nandakrishna; Amrutha, Cynthia (International Journal of Research in Medical Sciences, 2021)
Background: Cerebral venous and sinus thrombosis (CVT) is one of the common causes of stroke in young people. It is a relatively uncommon neurologic disorder that is potentially reversible with prompt diagnosis and appropriate medical care. The purpose of this study is to identify the clinical and radiological features aiding diagnosis of cortical vein thrombosis Methods: A cross-sectional study was conducted from November 2015 to May 2017 in tertiary care centre in Manipal after institutional ethical clearance. A total of 46 patients diagnosed with CVT were included in the study. Clinical symptoms and signs at admission and radiological features were documented. Results: A total of 46 subjects were included. Males (53.3%) were more affected than females (46.7%), mostly in the 3rd decade. The most common risk factors were polycythaemia (31.1%) and oral contraceptive pill intake (17.7%). Headache was the most common symptom followed by paralysis and seizures. Multiple sinuses were involved in two-thirds of the patients. Superior sagital sinus thrombosis was the most common sinus involved followed by transverse sinus thrombosis Conclusions: The most common clinical feature is headache followed by paresis and seizures. Superior saggital sinus thrombosis is more common than transverse and sigmoid sinus thrombosis in Indian population. Normal CT scan of brain doesn’t rule out cerebral venous sinus thrombosis.